Performance analysis of reactive and proactive routing protocols in MANET - Alubady, Raaid; Al-Samman, Mohammed; Habbal, Adib M. Monzer; Hassan, Suhaidi; Arif, Suki (Asian Research Publishing Network (ARPN), 2015)
In the artificial disaster field, Mobile Ad-hoc Network (MANET) routing is considered a challenging task because of the unpredictable changes in the network topology due to the absence of any centralized control. This routing has led to the development of several different routing protocols for MANET.Thus, it is hard to decide which of these protocols act better than the others.The objectives of this study are of two folds.First, this study provides a performance comparison of MANET routing protocols in terms of delay, packet lost, throughput, jitter, packet delivery ratio (PDR), and normalized routing load (NRL). Second, this study identifies whether MANET routing protocol has an impact on the artificial disaster and suggests which protocols may perform better.For experimental purposes, Network Simulator 2 (NS-2) was used.High density nodes were created in a 1000×1000m location area, and each node was assigned a CBR traffic load.Random Waypoint Mobility mode was used to be implemented with varying pause time and the number of connections.The simulation results show that Destination Sequence Distance Vector (DSDV) protocol provides better throughput and PDR with less jitter, delay and NRL for low or high-traffic load and mobility.However, DSDV still has performance limitations with packet loss parameter. Additionally, the results obtained show that DSDV gives a great improvement for using network resources, especially when the number of connections is high with low mobility. Hence, DSDV is considered as a better routing protocol that is used in the artificial disaster and emergency recovery application.